THE EFFECT OF “ENVIRONMENT” AS A FACTOR ON THE OUTCOMES OF LEVERAGING FIRM CAPABILITIES (Third Sector Social Economic Review, 2023)
In line with the important objectives of the firm, capabilities which include all kinds of processes, actions and skills to improve its performance (Bryson, Ackermann and Eden, 2007), and efficently transform input resources into outputs (Li, Shang ve Slaughter, 2010) are the most crucial resource of the resource-based view (Koçak, Özer ve Gürel, 2005). To generate a competitive advantage path, they need to be efficiently and effectively mobilized, coordinated and leveraged (Sirmon, Hitt and Ireland., 2007). One of the most important factors to which these transactions and their results depend, is the external environment of the firm. The performance of the different firm structures, processes and operations created and structured by dynamic-static environmental factors (Albring ve diğerleri, 2016; Iyer, Srivastava ve Rawwas 2014; Starik, 2013), which provide different opportunities and threats at the same time, will lead to different performances on leveraging the capabilities and creating competitive advantange. . In this research, which analyzes this context and tries to explain the outcomes, propositions are based on the type of strategy in which firms leverage their capabilities according to the external environment they are in, and these propositions are supported by both primary and secondary data by exploiting qualitative research method.
Keywords: Firm capabilities; resource advantage strategy; market opportunity strategy; entrepreneurial strategy